(untitled) (Anuario Filosófico, 2018)
This work examines Richard Kilvington’s Sophisma 47, in the context of the Doctrine of Obligations. Its aim is to revise the thesis of P. V. Spade, who attributes to Kilvington an intermediate position between Burley and Swyneshed, and interprets the Doctrine of Obligations in general as a Theory of Counterfactuals.